Sustainable manufacturing practices implementation in Malaysia industries - Hassan, Mohamad Ghozali; Nordin, Norani; Ashari, Hasbullah (Penerbit UTM Press, 2015)
Implementation of sustainable manufacturing practices brings lot of gains and benefits not alone to the manufacturing industries but also to their immediate environment.Such benefits includes increase the manufacturing capacity, good industry image, environmental friendly product, enhance business profile, consumer perceptions and corporate reputation.Nevertheless, many manufacturing industries are still unable to properly implements sustainable manufacturing practices.Hence, this paper identifies the sustainable manufacturing practices among manufacturing industries.Data were collected based on quantitative research method using self-administered questionnaires.A total of 104 manufacturing industries were selected based on stratified random sampling technique and SPSS was used to analyze the data.The result identified some applicable and non-applicable factors that affect proper implementation of sustainable manufacturing practices among manufacturing industries.Thus, the study will assist manufacturing industries to strengthen their implementation strategies on sustainable practices.